2021
DOI: 10.3390/su13042295
|View full text |Cite
|
Sign up to set email alerts
|

Strength Performance and Microstructure of Calcium Sulfoaluminate Cement-Stabilized Soft Soil

Abstract: Calcium sulfoaluminate cement (CSA) was used to stabilize a type of marine soft soil in Dalian China. Unconfined compressive strength (UCS) of CSA-stabilized soil was tested and compared to ordinary Portland cement (OPC); meanwhile the influence of amounts of gypsum in CSA and cement contents in stabilized soils on the strength of stabilized soils were investigated. X-ray diffraction (XRD) tests were employed to detect generated hydration products, and scanning electron microscopy (SEM) was conducted to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Ding et al (2019) studied the dynamic characteristics of frozen–thawed soil under cyclic loading using the dynamic triaxial test. Liu et al (2021) measured the unconfined compressive strength of submarine soft soil and analyzed the microstructure of the soil stabilized using the SEM technique. Using SEM, Watabe and Saitoh (2015) found that the high porosity of natural clay soils was not only due to the high initial water content but also the sedimentation of flocculation, which played an important role in the formation of the microfabric of natural clay soils.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al (2019) studied the dynamic characteristics of frozen–thawed soil under cyclic loading using the dynamic triaxial test. Liu et al (2021) measured the unconfined compressive strength of submarine soft soil and analyzed the microstructure of the soil stabilized using the SEM technique. Using SEM, Watabe and Saitoh (2015) found that the high porosity of natural clay soils was not only due to the high initial water content but also the sedimentation of flocculation, which played an important role in the formation of the microfabric of natural clay soils.…”
Section: Introductionmentioning
confidence: 99%
“…After comprehensive investigation, solidification technology is currently the most widely used, economical, and cost-effective method in the utilization of waste soil. Chemical treatment with traditional stabilizers such as lime and cement can effectively alter several basic engineering properties of soils [5]. However, cement stabilization in soils may increase the stiffness and may lead to brittle soil behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Ye’elimite, also known as tetracalcium trialuminate sulfate, is the dominant mineral in calcium sulfoaluminate (CSA) cement and exhibits high tailored dimensional expansion and early strength [ 1 , 2 , 3 ]. Since the 1970s, CSA cement has been widely used as a rapid repairing material and has recently been promoted for use in numerous domains, including soft soil stabilization and three-dimensional printing [ 4 , 5 , 6 ]. Moreover, CSA cement has been considered a promising alternative binder owing to its lower CO 2 emissions and energy consumption compared with Portland cement, in which ye’elimite plays an essential role [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%